SOLAR PANEL BASED 10000 mAH POWER BANK - Siahaan, Goklas Miracle (Universitas Muhammadiyah Semarang, 2024)
Solar energy is the largest source of energy on earth. Every day, heat is emitted to our earth, with a capacity of 1.7 x 1014 kilowatts (kW), or equivalent to burning 6 million tons of new rock every second. Solar cells (photovoltaic) PV is a semi-conductor technology that was developed as a power generator. The basic principle of this PV origin is the opposite originating from an LED (light emitting diode) which replaces electric power into light or can be said to be identical to a light diode (photodiode) p-n junction or (p-n junction). The function of the solar cell is to charge the battery, where the battery functions as a power source to turn on the system on the equipment used. The sunlight enters the solar cell which is converted into electrical energy and the energy is stored in the battery to store electrical energy when sunlight is available, connected to the USB driver power bank module and the micro USB module. The USB driver power bank module can function as an output when charging the cellphone.